Particular issues of analysis of collisions of the current land legislation - Dorosh, Y.; Dorosh, O.; Avramchuk, B.; Barvinskyi, A.; Demchuk, V. (Land Management, Cadastre and Land Monitoring, 2021)
The article analyzes the main legal conflicts that arose as a result of the adoption of changes to the land legislation of Ukraine during 2020-2021.It was found that the transfer of land for use requires a permit for the development of technical documentation on land management to establish (restore) the boundaries of land in kind (on the ground). At the same time, there is another conflict - the specified technical documentation performs the same function as the land management project for the allocation of land for use.As a result of the analysis of amendments to the Law of Ukraine "On Land Management", it is established that the wording of the text of the article in terms of the basis of work has two interpretations, the first of which concerns privately owned land, and the second - state and municipal land in use.In addition, it was found that in the latest versions of regulations, the terms "owner" and "owner (manager)" meet next to each other, which allows us to state that the authors of the regulation aimed to separate the disposal of private land from one on the one hand and state and communal - on the other.Key words: legislative acts, land plots, land management, division (association) of land plots, privatization of land plots.